Direct and correlated responses to selection for daily gain in rabbits - Sanchez, J. P.; Baselga, M.; Silvestre, Miguel A.; Sahuquillo, J. (World Rabbit Science Association, 2021)
In a selection experiment for daily gain, direct and correlated responses were estimated, using a cryopreserved population as control. The difference between the selected and control group was 15 generations. The direct response for daily gain was 0.18 g./d. per generation and we did not find correlated response for feed conversion. These results are worse than expected. This could be due to the effect of the special diet used to control the enterocolitis disease.